Migrações para assentamentos rurais: Analisando as trajetórias de assentados no município de Padre Bernardo no Estado de Goiás Brasil - Oliveira, Marcelo Leles Romarco de (2012)
This work is the result of a case study that analyzes the trajectories of migrants to rural settlements located in the municipality of Padre Bernardo, the region surrounding the Federal District, Goiás State in this region several settlements created in the late 90's, were consisting of workers of rural origin who migrated from various regions of Brazil to work, especially in services and construction in Brasilia before reaching settlements. Thus, the text aims to give some reflections on understanding the dynamics of migration to rural settlements in Brazil trajectories with rural-city-settlements. As consideration, it was noticed that after many years or even decades living in the city, these migrants decide to join the struggle for land and depart for land occupation in the region. In the settlement, the settlers are facing a new challenge that will be built collectively and individually